Sesat Pikir Aplikasi Hermeneutika Hukum Menurut Hans-Georg Gadamer - Manullang, Fernando Morganda (Jurnal Hukum & Pembangunan, 2018)
Some legal writing written by legal scholars interpret legal text methodologically in their analysis, while seeking its philosophical foundation, namely Hans-Georg Gadamer’s legal hermeneutics. Such hermeneutics is part of Gadamer’s philosophical hermeneutics which can be applied to law, aside from theology and philology. Such hermeneutics employs in general and on ontological level thereof. Such understanding is unknown in jurisprudence, because the interpretation in jurisprudence is more methodological, an idea that Gadamer clearly opposes. Such scholarly legal perspective potentially creates some fallacies towards Gadamer's idea on legal hermeneutics